Observations of the Origin of Downward Terrestrial Gamma‐Ray Flashes. Issue 23 (10th December 2020) - Belz, J. W.; Krehbiel, P. R.; Remington, J.; Stanley, M. A.; Abbasi, R. U.; LeVon, R.; Rison, W.; Rodeheffer, D.; Abu‐Zayyad, T.; Allen, M.; Barcikowski, E.; Bergman, D. R.; et al.
Abstract: In this paper we report the first close, high‐resolution observations of downward‐directed terrestrial gamma‐ray flashes (TGFs) detected by the large‐area Telescope Array cosmic ray observatory, obtained in conjunction with broadband VHF interferometer and fast electric field change measurements of the parent discharge. The results show that the TGFs occur during strong initial breakdown pulses (IBPs) in the first few milliseconds of negative cloud‐to‐ground and low‐altitude intracloud flashes and that the IBPs are produced by a newly identified streamer‐based discharge process called fast negative breakdown. The observations indicate the relativistic runaway electron avalanches (RREAs) responsible for producing the TGFs are initiated by embedded spark‐like transient conducting events (TCEs) within the fast streamer system and potentially also by individual fast streamers themselves. The TCEs are inferred to be the cause of impulsive sub‐pulses that are characteristic features of classic IBP sferics. Additional development of the avalanches would be facilitated by the enhanced electric field ahead of the advancing front of the fast negative breakdown. In addition to showing the nature of IBPs and their enigmatic sub‐pulses, the observations also provide a possible explanation for the unsolved question of how the streamer to leader transition occurs during the initial negative breakdown, namely, as a result of strong currents flowing in the final stage of successive IBPs, extending backward through both the IBP itself and the negative streamer breakdown preceding the IBP. Key Points: Downward Terrestrial Gamma‐ray Flashes occur during strong initial breakdown pulses of negative cloud‐to‐ground and cloud lightning The initial breakdown pulses consist of streamer‐based fast negative breakdown having transient sub‐pulse conducting events or "sparks" The streamer to leader transition of negative stepping occurs during strong currents in the final stage of initial breakdown pulses